Poly(vinyl alcohol): An Economical Substitute to Calcium Lignosulphonate for PVC/PET Separation by Froth Flotation - Shafeeq, Amir; Aslam, Rabya; Ali Shahid, Shaukat; Muhammad, Ayyaz; Ijaz, Aamir; Mehmood Ali, Arshid; Ullah, Inam; Mushtaq, Muhammad; Rashid, Umer (Asian Journal of Chemistry, 2013)
The environmental and economic concerns have lead to the development of a number of management techniques to handle the waste polymers. Although recycling is considered as one of the most feasible solution to cater the plastic waste yet it is not implemented widely due to high cost involved in the process. Polyethylene terephthalate (PET) is one of the most recycled polymer, however, its separation from other polymers is necessary step prior to the recycling process. The separation of PVC/PET mixture by froth flotation technique using poly(vinyl alcohol) as an economical substitute of calcium lignosulphonate as wetting agent in separation of PVC from PET/PVC mixture using froth flotation technique is studied in the present work. The conditions such as pH of wetting solution, separation time, composition and air velocity were optimized and results were compared with previously used calcium lignosulphonate as wetting agent. The re-usage of PVA showed consistent results, repeatedly for eight times, with high separation efficiency up to 80 % and proved an economical substitute of calcium lignosulphonate as wetting agent in separation of PVC from PET/PVC mixture using froth flotation technique.